A comparative study of associated risk factors of overweight in normal and overweight children of 12-16 years of age - Patil, Mohan A.; Rana, Ritu Raj (International Journal of Contemporary Pediatrics, 2018)
Background: In 21st century childhood obesity has become one of the most serious public health problem. This now a global problem and affecting all the countries of the world. Overweight and obesity in children and adolescent is defined by American medical association as BMI between 85-95 centile and BMI >95th centile respectively for children aged 2-16 years. Risk factors for overweight and obesity in children are different for different regions, places, cultures and food habits of different people and society. New factors are coming up due to economic prosperity and change in lifestyle of the young population. Habit formation occurs mainly during childhood and adolescence so primary intervention targeting this age group has high possibility of yielding good results. Methods: A comparative study of associated risk factors of overweight and obesity was conducted in D. Y. Patil Medical College in Children’s age 12-16 years. The independent variable (parameters) for the study were age, gender, type of family, paternal education, maternal education, father’s occupation, mother’s occupation, socio-economic status, at least one overweight parent, sleeping time, TV viewing time, type of food, mode of transport to reach school, frequency of eating out and level of physical activity. Children were given questionnaire that was filled by their parents and return back to us. Results: The analysis revealed that at least one overweight parent, mode of transport to reach school and frequency of eating out are associated with obesity while TV viewing duration and level of physical activity are strongly associated with obesity. Conclusions: Childhood obesity is a chronic multifactorial medical condition. Its risk can be significantly reduced by avoiding and preventing some factors.